INVESTIGATION OF IONIC LIQUIDS AS TERMODYNAMIC AND KINETIC METHANE HYDRATE INHIBITORS - NASHED, OMAR (2014)
The formation of gas hydrates in gas; production and transmission pipelines leads to severe safety problems and huge economic loss, which has been the subject of long-standing problems. As exploration and production moves to deeper seas, temperature and pressure conditions in the field favors hydrate formation. In this dissertation, the performance of nine ionic liquids (ILs) was investigated as thermodynamic and kinetic gas hydrate inhibitors. The hydrate dissociation temperature and induction time were determined for methane gas hydrates using a high pressure micro deferential scanning calorimeter. All the ionic liquids weretested at a concentration 10 wt% for thermodynamic study. Two best screened ionic liquids as thermodynamic inhibitors were further investigated at various concentrations and their performance was compared with commercially available inhibitors.